Comparing the toxicity effect induced by Bisphenol A and Bisphenol S in the zebrafish model - Saad, Muhamad Fikri Shazlan; Abdullah, Muhammad Nazrul Hakim; Lim, Vuanghao; Yong, Yoke Keong (Dr Tarak Nath Podder Memorial Foundation, 2025)
Introduction: Bisphenol S (BPS) is structurally similar to bisphenol A (BPA), and with the shift from BPA to BPS in consumer products, knowledge of BPS's impact on human health remains limited. This study compares the toxicity of BPA and BPS in zebrafish embryos. The zebrafish embryo model, with conserved vertebrate cardiac development and high sensitivity to environmental toxins, provides an ideal platform to evaluate the comparative safety of BPS. Methods: Zebrafish embryos were exposed to BPA and BPS at concentrations of 10 µM and 20 µM in 24-well plates. Mortality rates were assessed at 120 hours post-fertilisation (hpf). Hatching rates were evaluated at 72 and 96 hpf using a modified protocol. Cardiotoxicity was assessed by measuring heart rate and pericardial oedema at 96 hpf. Results and Discussion: Neither BPA nor BPS had a significant effect on mortality or hatching rates. In the cardiotoxicity assay, exposure to 10 µM BPA increased the heart rate, while 20 µM BPA significantly (p<0.05) reduced it. Both BPS concentrations did not significantly (p>0.05) affect the heart rate compared to the control. Pericardial oedema was observed in both BPA-treated groups (10 µM and 20 µM) but not in the BPS-treated groups. Conclusion: BPS exhibits lower toxicity than BPA with respect to mortality and cardiotoxicity in zebrafish embryos, although neither compound affected hatching rates.